Harmonization of Mythology into the Poetry of the Modern Poets: A Study on the Selected Poems of Yeats, Eliot and Auden - E HOSNE ARA, JANNAT (International Journal of Language and Literary Studies, 2022)
This research is an endeavour to explore the poetry of the three prevalent modern poets William Butler Yeats, Thomas Sterns Eliot and Wystan Hugh Auden, through the lenses of their harmonization of mythology. Though they belong to the modern period in English literature, they reference different types of myths as they teach us moral lessons and profound purpose, explain historical events and add creativity to literary pieces. This study searches for the reason why and how the poets incorporate the usage of mythology into their poetry. In this paper, the writer will allude to some of the lines of different poems of the three poets above. Through the reference of these poems, the reader will come to understand with what purpose the poets integrate the representation of mythology into their poems. Specifically, this research will focus on the poetry of the modern poets. These three poet depict their poems with mythology in their own way. They always try to deploy different myths into their poems as these are very meaningful and purposeful to our life still. Our selected three poets more or less experience both the WWI and WWII and the after effects of these two massive war make them to contemplate for the people, the country and the world. They ruminate on the contemporary devastative circumstances of the world. Through exhibiting various mythical allusions into their poetry, they attempt to rekindle peace and complacency all over the world. The researcher captures evidence from textual reference to support her opinion regarding the related issues. This paper attempts to expose the related reasons why and how the modern poets delineate mythology into their poetry.